THE VULNERABILITY OF THE DIGITAL NATIVE GENERATION TO HIV/AIDS INFECTION: A CONCEPT ANALYSIS - Umam, Moh. Khotibul; Setiawan, Agus; Permatasari, Henny; Mansyur, Muchtaruddin (Nurse and Health: Jurnal Keperawatan, 2024)
Background: The digital native generation is the current generation of young people who are very familiar with the internet and gadget applications. This makes them vulnerable to the risk of disease transmission, both directly and indirectly. Objective: The study aimed to analyze the concept of the vulnerability of digital natives, or young adults, to HIV/AIDS. Methods: This study used the 8-step concept analysis framework developed by Walker and Avant, along with a comprehensive literature review done across three databases: google scholar, ProQuest, and ScienceDirect. The systematic literature reviewed included papers published between 2008 to 2022. Results: The concept identification findings derived from a comprehensive evaluation of 16 papers indicate that the defining features include individual characteristics, social factors, structural problems, and health programs. Conclusion: The digital generation, characterized by their convenient access to the internet and digital media, has a greater vulnerability to HIV/AIDS transmission as a result of engaging in hazardous behaviors and participating in health initiatives. The use of digital media in intervention programs has the potential to decrease healthcare expenditures and improve the efficacy of HIV/STI control measures.